2022
DOI: 10.1021/acs.est.1c08842
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Carbon Nanotube Network Membranes for Membrane Distillation: High-Throughput Performance and Transport Mechanism

Abstract: Despite increasing sustainable water purification, current desalination membranes still suffer from insufficient permeability and treatment efficiency, greatly hindering extensive practical applications. In this work, we provide a new membrane design protocol and molecule-level mechanistic understanding of vapor transport for the treatment of hypersaline waters via a membrane distillation process by rationally fabricating more robust metal-based carbon nanotube (CNT) network membranes, featuring a superhydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 58 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Much‐enhanced flux was attributed to the achievement of very low liquid‐solid contact (accounting for only 3.23% of the superhydrophobic interface with a water contact angle of 170°) that enabled water vapor to rapidly move through the membrane structure and effectively resist saline feed by creating a Cassie‐Baxter state. [ 187 ] The enhancement in flux was also elaborated by AN et al hypothesizing that CNTs facilitated the mass transfer of vapors in an electrospun PVDF membrane via various mechanisms such as Knudsen diffusion (molecule−wall collision), viscous flow (molecule–molecule collision), and molecular diffusion. [ 188 ] Xie et al utilized the spray coating method to deposit distinct amounts of CNTs on three commercial microporous polymer membranes (PTFE, PVDF, and PP) and reported a threefold increase in water flux for the CNT‐deposited PTFE membranes, which was attributed to the increase in its specific surface area.…”
Section: Most Widely Used Nms For MD Membranesmentioning
confidence: 99%
“…Much‐enhanced flux was attributed to the achievement of very low liquid‐solid contact (accounting for only 3.23% of the superhydrophobic interface with a water contact angle of 170°) that enabled water vapor to rapidly move through the membrane structure and effectively resist saline feed by creating a Cassie‐Baxter state. [ 187 ] The enhancement in flux was also elaborated by AN et al hypothesizing that CNTs facilitated the mass transfer of vapors in an electrospun PVDF membrane via various mechanisms such as Knudsen diffusion (molecule−wall collision), viscous flow (molecule–molecule collision), and molecular diffusion. [ 188 ] Xie et al utilized the spray coating method to deposit distinct amounts of CNTs on three commercial microporous polymer membranes (PTFE, PVDF, and PP) and reported a threefold increase in water flux for the CNT‐deposited PTFE membranes, which was attributed to the increase in its specific surface area.…”
Section: Most Widely Used Nms For MD Membranesmentioning
confidence: 99%
“…However, membrane failure, including pore wetting and mineral scaling, has greatly restricted its potential and thus has become a prolonged and prominent concern for the scientific community. , Intensive investigations have revealed that constructing a micro/nanoscale re-entrant texture with low interfacial energy is the key to achieving a unique anti-wettability surface with enhanced wetting and scaling resistance. ,, A common approach involves an initial substrate construction (e.g., poly­(vinylidene difluoride) [PVDF]), ,, subsequent deposition of nanomaterials (e.g., TiO 2 , SiO 2 , carbon nanotubes, etc. ,,, ), and final surface fluorination. ,,, Despite its prevalence, such a procedure exhibits some potential risks. For instance, the chemical inertness of PVDF generally requires an indispensable surface activation step under extremely alkaline conditions, , thus introducing a reactive or ionic site for binding nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…On the selfcleaning superhydrophobic surface, water droplets can easily roll and simultaneously carry away dust/dirt attached to the surface. Moreover, superhydrophobic materials have been developed from various materials, such as carbon nano-structures [22][23][24], silica-based nano-composites [25][26][27][28], fluorinated silanes [29][30][31], siloxane polymers [32][33][34] and twodimensional (2D) transition metal dichalcogenides [35]. Significant efforts have been made in developing self-cleaning superhydrophobic surfaces [19].…”
Section: Introductionmentioning
confidence: 99%